The efficacy and safety of ipriflavone in postmenopausal women with osteopenia or osteoporosis: A systematic review and meta-analysis. (September 2020) - Hu, Qinsheng; Long, Cheng; Wu, Diwei; You, Xuanhe; Ran, Liyu; Xu, Jiazhuang; O Klineberg, Eric; Huang, Shishu; Chen, Jiali; Ning, Ning
Graphical abstract: Abstract: Objectives: Ipriflavone (IP) is one of the over-the-counter drugs and found in foods, which is available for prevention of osteoporosis (OP) since 1989 in over 22 countries. Although some clinical trials have suggested that IP is appropriate for treatment of OP, there continues to be controversy regarding the efficacy and safety due to some contradictory reports. With the wide usage of IP for osteoporotic women, there is a critical need for evaluation of the evidence for IP in clinical practice. Methods and materials: We searched randomized control trials (RCTs) in PubMed, CENTRAL and CNKI which used the regimen of IP in postmenopausal women with osteopenia or OP. The efficacy referred to the absolute change and relative change in bone mineral density (BMD) and bone turnover markers. The safety profiles were associated with adverse events and the number of subject withdrawals due to adverse reactions. results: Eleven RCTs ( n = 1605) met the eligibility criteria were included. The increase of the BMD in lumbar spine of the IP group is greater than that of the placebo group (random effect model: SMD = 0.36; 95%CI= (0.09, 0.62)). For safety profile, most frequent reactions are gastrointestinal symptoms, but withdrawals due to adverse reactions are similar in both the IP group and placebo control at the same time intervals. Conclusions: IP significantly increases BMD and has inhibitory effect on bone resorption markers in postmenopausal women with osteopenia or OP. Gastrointestinal symptoms may occur, but adverse drug withdrawal events were not statistically increased when compared with placebo group.